Factors Influencing Third Party Logistics Performance in Malaysia: The Role of Trust as a Mediator - Gunalan SO Nadarajah (International Journal of Supply Chain Management, 2015)
This conceptual paper examines the influence of specific investments,opportunistic behavior, prior satisfaction, 3PL reputation, reciprocity andcommunication on outcomes of third-party Logistics performance, and the extentto which trust affects these relationships. The studies undertaken thus far are more towards evaluating 3PLperformance through some defined critical success indicators which is believedcan only derive short term benefits. Long terms success of 3PL by taking intoconsideration of relationship marketing has been neglected. Since most of the studies thus far onlytalks about performance based on short term achievements and very littleconsideration given on long term performance, thus this research will look intoPerformance evaluation (Dependent Variable) and aspects contributing to longterm success via relationship marketing.